Unraveling nonadiabatic ionization and Coulomb potential effect in strong-field photoelectron holography - Song, X. H.; Lin, C.; Sheng, Z. H.; Liu, P.; Chen, Z. J.; Yang, W. F.; Hu, S. L.; Lin, Chii D.; Chen, J. (My University, 2016)
Strong field photoelectron holography has been proposed as a means for interrogating the spatial and temporal information of electrons and ions in a dynamic system. After ionization, part of the electron wave packet may directly go to the detector (the reference wave), while another part may be driven back and scatters off the ion(the signal wave). The interference hologram of the two waves may be used to extract target information embedded in the collision process. Unlike conventional optical holography, however, propagation of the electron wave packet is affected by the Coulomb potential as well as by the laser field. In addition, electrons are emitted over the whole laser pulse duration, thus multiple interferences may occur. In this work, we used a generalized quantum-trajectory Monte Carlo method to investigate the effect of Coulomb potential and the nonadiabatic subcycle ionization on the photoelectron hologram. We showed that photoelectron hologram can be well described only when the effect of nonadiabatic ionization is accounted for, and Coulomb potential can be neglected only in the tunnel ionization regime. Our results help paving the way for establishing photoelectron holography for probing spatial and dynamic properties of atoms and molecules.
Citation: Song, X. H., Lin, C., Sheng, Z. H., Liu, P., Chen, Z. J., Yang, W. F., . . . Chen, J. (2016). Unraveling nonadiabatic ionization and Coulomb potential effect in strong-field photoelectron holography. Scientific Reports, 6, 10. doi:10.1038/srep28392
Keywords: Induced Electron-Diffraction; Above-Threshold-Ionization; Laser; Photoionization; Atoms; Phase